Bonding personal social capital as an ingredient for positive aging and mental well-being. A study among a sample of Dutch elderly. (1st December 2020) - Simons, Marianne; Lataster, Johan; Reijnders, Jennifer; Peeters, Sanne; Janssens, Mayke; Jacobs, Nele
Abstract: Objectives: The current study aims to add to the limited empirical research of possible benefits of personal social capital for the well-being of elderly. A validated personal social capital scale, measuring both bonding and bridging social capital in a general population, was adjusted to fit the characteristics of the social environment of elderly, to explore the association between social capital and well-being of elderly, as well as the mediating role of loneliness. Method: A sample of 328 Dutch adults, varying in age from 65 to 90 years ( Mean  = 72.07; SD  = 4.90) filled out an online questionnaire including the adapted personal social capital scale for elderly (PSCSE), as well as validated scales measuring social, emotional, and psychological well-being and loneliness. Relevant other (demographic) variables were included for testing construct and criterion validity. Results: CFA analysis revealed the subdimensions bonding and bridging social capital with reliability scores of respectively α  = .88 and α  = .87, and α  = .89 for the total scale. Regression analyses confirmed construct and criterion validity. Subsequently, significant positive associations between bondin g social capital and respectively social, emotional and psychological well-being were found. These associations were mediated by loneliness . Bridging social capital was only found to be significantly associated with social well-being, not mediated by loneliness. Conclusion: Our findings have enhanced our understanding of the association between social capital and mental well-being of elderly and indicate that bonding personal social capital in particular may be considered an ingredient for positive aging.